FLOWERS SALE PREDICTION USING MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
India's culture is described by fusion. Nearly every day is a festival in this diverse, multicultural country where people speak hundreds of languages, practice dozens of religions, and belong to different ethnic groups. So, flowers play a major role at these celebrations. Flowers and floral arrangements are highly sought after items in both rituals and gifts. There is a variation of how flowers are used daily, meaning they aren't always used for rituals and gifts. Using machine learning, we can find out what influences Flowers sales and estimate future sales. In terms of the efficiency of the machine learning algorithms used for prediction, the conclusions are discussed. The system's main goal is to study future flower market sales and predict whether they will increase or decrease using various machine learning methods such as Gradient Boosted and Decision Trees.